1994
DOI: 10.1111/j.1479-828x.1994.tb01041.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Polycystic Ovaries on Ultrasound Scanning in a Population of Randomly Selected Women

Abstract: Polycystic ovaries (PCO) diagnosed by ultrasound have been commonly reported amongst healthy women. The study aimed to determine the prevalence of PCO in a population of women from the community, and to relate it to clinical and endocrinological data. Twelve hundred women chosen randomly from electoral rolls were invited to take part in the study. Two hundred and fifty five women (21%) who met eligibility criteria greed to participate and 183 women 916%) finally completed the study. Seventy two women did not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
113
2
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(124 citation statements)
references
References 22 publications
5
113
2
4
Order By: Relevance
“…Epidemiological studies have resulted in estimates of prevalence, in women of reproductive age, that range from 6.5% to 8% using biochemical and/or clinical evidence, [4][5][6][7] and ultrasound-based studies have reported a prevalence of 20% or more. [8][9][10][11] Therefore, in a population of seven million Canadian women aged between 15 and 44 years, as many as 1.4 million women may be afflicted with this disorder. 12 It has been our experience that many, if not most, women are first given a diagnosis of PCOS when they present to a reproductive endocrinologist with infertility, and that in the years following last delivery and continuing to reproductive senescence there is a clear tendency to forgo long-term management of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have resulted in estimates of prevalence, in women of reproductive age, that range from 6.5% to 8% using biochemical and/or clinical evidence, [4][5][6][7] and ultrasound-based studies have reported a prevalence of 20% or more. [8][9][10][11] Therefore, in a population of seven million Canadian women aged between 15 and 44 years, as many as 1.4 million women may be afflicted with this disorder. 12 It has been our experience that many, if not most, women are first given a diagnosis of PCOS when they present to a reproductive endocrinologist with infertility, and that in the years following last delivery and continuing to reproductive senescence there is a clear tendency to forgo long-term management of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using trols of the CASH study 18 : 0.94% reported physiciandiagnosed polycystic ovaries or SLS, and 27.2% of ultrasound to address the question of population prevalence of polycystic ovary morphology (a component those with SLS reported a history of infertility (defined as ''unsuccessful attempts to get pregnant for two or of SLS, but not exclusive to or definitive for the disorder), 21 have suffered from either low response more years''). Farquhar et al 23 have suggested that women with rates, 22,23 or biased ascertainment of cases.…”
Section: / 7b4b$$0852mentioning
confidence: 99%
“…Studies using ultrasonography to identify the presence of polycystic ovaries have reported prevalence rates of 21 -22% among randomly selected women (5). Although menstrual cycle disturbance and hyperandrogenism are more common in women with polycystic ovaries it is generally accepted that many women with polycystic ovaries are endocrinologically normal.…”
Section: Introductionmentioning
confidence: 99%